2019
DOI: 10.1002/jcp.29027
|View full text |Cite
|
Sign up to set email alerts
|

The survivin molecule as a double‐edged sword in cellular physiologic and pathologic conditions and its role as a potential biomarker and therapeutic target in cancer

Abstract: Survivin is a member of the family of apoptosis inhibitory proteins with increased expression level in most cancerous tissues. Evidence shows that survivin plays regulatory roles in proliferation or survival of normal adult cells, principally vascular endothelial cells, T lymphocytes, primitive hematopoietic cells, and polymorphonuclear neutrophils. Survivin antiapoptotic role is, directly and indirectly, related to caspase proteins and shows its role in cell division through the chromosomal passenger complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 203 publications
(279 reference statements)
0
33
0
Order By: Relevance
“…Previous reported showed that survivin is predominantly localized in the cytoplasm of cancer cells and is generally believed to function as apoptotic suppressor to maintain survival of cancer cells. In contrast, the smaller fraction of nuclear localized survivin is considered to act as a component of CPC complex to promote cell cycle progression, suggesting that the different subcellular pools of survivin exhibit distinct biological functions (13)(14)(15)(16). Thus, as an oncoprotein that is both essential for mitosis and apoptosis inhibition, survivin seemed a promising novel target for anti-cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reported showed that survivin is predominantly localized in the cytoplasm of cancer cells and is generally believed to function as apoptotic suppressor to maintain survival of cancer cells. In contrast, the smaller fraction of nuclear localized survivin is considered to act as a component of CPC complex to promote cell cycle progression, suggesting that the different subcellular pools of survivin exhibit distinct biological functions (13)(14)(15)(16). Thus, as an oncoprotein that is both essential for mitosis and apoptosis inhibition, survivin seemed a promising novel target for anti-cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential target oncogenes, including Yes-associated protein [54], which is a member of the Hippo signaling pathway contributing to organ size control and tumorigenesis, have emerged as attractive targets for cancer therapeutics for liver cancer [55,56]. Survivin, which is a member of the family of apoptosis inhibitory proteins, has increased expression in various cancers [57] and, as a result, has been considered as a potential biomarker and therapeutic target for HCC gene therapy [58].…”
Section: Oncogenesmentioning
confidence: 99%
“…Previous reported showed that survivin is predominantly localized in the cytoplasm of cancer cells and is generally believed to function as apoptotic suppressor to maintain survival of cancer cells. In contrast, the smaller fraction of nuclear localized survivin is considered to act as a component of CPC complex to promote cell cycle progression, suggesting that the different subcellular pools of survivin exhibit distinct biological functions [13][14][15][16]. Thus, as an oncoprotein that is both essential for mitosis and apoptosis inhibition, survivin seemed a promising novel target for anticancer treatment.…”
Section: Introductionmentioning
confidence: 99%